2013
DOI: 10.1111/bcp.12126
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the dose–response relationship of allopurinol: predicting the optimal dosage

Abstract: AIMSThe aim of the study was to identify and quantify factors that control the plasma concentrations of urate during allopurinol treatment and to predict optimal doses of allopurinol. METHODSPlasma concentrations of urate and creatinine (112 samples, 46 patients) before and during treatment with various doses of allopurinol (50-600 mg daily) were monitored. Non-linear and multiple linear regression equations were used to examine the relationships between allopurinol dose (D), creatinine clearance (CLcr) and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 32 publications
(59 reference statements)
1
36
1
1
Order By: Relevance
“…8 AHS led to a renal clearance-based dosing algorithm, 31 which generally restricted ALLO dosing to levels ineffective for most patients. 32,33 Recent US guidelines have relaxed the dosing limitations on ALLO for patients, including those with renal impairment, provided there is adequate patient education and monitoring. 8 However, ALLO dosing 4300 mg/d is uncommon (o10% of ALLO patients), even given that o50% of patients treated with ALLO 300 mg/d achieve target sUA levels.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 AHS led to a renal clearance-based dosing algorithm, 31 which generally restricted ALLO dosing to levels ineffective for most patients. 32,33 Recent US guidelines have relaxed the dosing limitations on ALLO for patients, including those with renal impairment, provided there is adequate patient education and monitoring. 8 However, ALLO dosing 4300 mg/d is uncommon (o10% of ALLO patients), even given that o50% of patients treated with ALLO 300 mg/d achieve target sUA levels.…”
Section: Treatmentsmentioning
confidence: 99%
“…Recent studies have reported the benefits of ALLO titration to higher daily dosages. 33,58,59 No treatment-related adverse event costs, aside from those related to ALLO AHS, were included in the budget impact analysis. This was justified based on similar adverse event rates for FEBUX and ALLO from clinical trial data.…”
Section: Limitationsmentioning
confidence: 99%
“…Whether genetic variation in these genes also influences renal oxypurinol clearance and thus the clinical response, or lack of response to allopurinol, is the subject of current research. The recognition that serum urate prior to allopurinol therapy is a key determinant of allopurinol dose required to reach the target serum urate in gout [7] provides further evidence that genetic variants influencing urate may also have a role in allopurinol response to therapeutic interventions.…”
Section: Allopurinol Metabolism and Role Of The Kidneymentioning
confidence: 99%
“…Thus, the decrease in renal function leads to higher plasma concentration of oxypurinol but in turn does not lead to greater inhibition of XO. Indeed, greater inhibition of urate synthesis is required to counter the decreased urate clearance associated with renal impairment [41].…”
Section: Canakinumabmentioning
confidence: 99%
“…Dose adjustment of allopurinol according to creatinine clearance is controversial. It often does not allow for reaching the recommended urate target of 6 mg/dl [41,87]. In this case, the patient should be switched to another ULT, such as febuxostat.…”
Section: Expert Opinionmentioning
confidence: 99%